2000
DOI: 10.1159/000029162
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Suicide in a Predominantly Caucasian Tropical/Subtropical Region of Australia

Abstract: Seasonal variations in suicide were examined in a Caucasian population living relatively close to the equator. A spring/early summer peak, but no secondary autumn peak, was found for males. An autumn trough was found for females. No significant seasonal variation was found for rurality, distance from the equator, employment status, or methods of suicide. Post-mortem blood alcohol levels were higher in spring and summer, possibly reflecting socialization patterns. The modest associations are consistent with sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
5
23
0
1
Order By: Relevance
“…It should be emphasized that the annual pattern in the total number of deaths, independent of cause, differed from that of death due to suicide: the peak of the former occurred in all three areas of Brazil during the autumn and/ or winter. The seasonal variation of suicide rates in the south of Brazil, with a significant peak in late spring/early summer, is like that in the northern (Eastwood & Peacocke, 1976;Fossey & Shapiro, 1992;Goodwin & Jamison, 1990) and southern (Cantor et al, 2000;Flisher et al, 1998;Heerlein et al, 2006;Lambert et al, 2003;Lester, 1991;Parker & Walter, 1982;Retamal et al, 1997;Rock et al, 2003) hemispheres. Geophysical and climatic conditions might therefore play a role in the determination of such variations, independent of hemisphere.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It should be emphasized that the annual pattern in the total number of deaths, independent of cause, differed from that of death due to suicide: the peak of the former occurred in all three areas of Brazil during the autumn and/ or winter. The seasonal variation of suicide rates in the south of Brazil, with a significant peak in late spring/early summer, is like that in the northern (Eastwood & Peacocke, 1976;Fossey & Shapiro, 1992;Goodwin & Jamison, 1990) and southern (Cantor et al, 2000;Flisher et al, 1998;Heerlein et al, 2006;Lambert et al, 2003;Lester, 1991;Parker & Walter, 1982;Retamal et al, 1997;Rock et al, 2003) hemispheres. Geophysical and climatic conditions might therefore play a role in the determination of such variations, independent of hemisphere.…”
Section: Discussionmentioning
confidence: 81%
“…In the northern hemisphere, the seasonal suicide incidence has been reported to have one peak in spring for men and two peaks, one in spring and the other in autumn, for women (Eastwood & Peacocke, 1976;Hakko et al, 1998a;Meares et al, 1981;Parker & Walter, 1982). In Australia, an autumn trough for women and a spring/early summer peak for males has been reported (Cantor et al, 2000). However, one peak in spring or summer, without sex differences, has also been found in the United States (Lester & Frank, 1988) and Hong Kong and Taiwan (Ho et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that increased suicide risk in persons with allergy may share a link with the wellestablished seasonality of suicide, with peaks in suicide mortality during spring time (when aeroallergens are at their highest) being reported consistently in the literature. 32,33 Reasons for this may be that increased pollen in the air during spring causes sensitized people Copyright (c) Oceanside Publications, Inc. All rights reserved. For permission to copy go to https://www.oceansidepubl.com/permission.htm to feel unwell and triggers the immune-related expression of inflammatory cytokines, which may be responsible for feelings of anxiety, depression, aggression, and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In an equatorial region, Parker et al [14] found no seasonal patterning of suicidal deaths. However, Cantor et al [15] studied seasonal variations of suicides in a Caucasian population living relatively close to the equator. They found a spring/early summer peak, but not a secondary autumn peak for males.…”
Section: Introductionmentioning
confidence: 99%